The introduction of an N-glycosylation site into prochymosin greatly enhances its production and secretion by Pichia pastoris - Wang, Nan; Yang, Caifeng; Peng, Huakang; Guo, Wenfang; Wang, Mengqi; Li, Gangqiang; Liu, Dehu (Microbial cell factories, 2022)
N-glycosylation is one of the most important post-translational modifications. Many studies have shown that N-glycosylation has a significant effect on the secretion level of heterologous glycoproteins in yeast cells. However, there have been few studies reporting a clear and unified explanation for the intracellular mechanism that N-glycosylation affect the secretion of heterologous glycoproteins so far. Pichia pastoris is an important microbial cell factory producing heterologous protein. It is of great significance to study the effect of N-glycosylation on the secretion level of heterologous protein. Camel chymosin is a glycoprotein with higher application potential in cheese manufacturing industry. We have expressed camel prochymosin in P. pastoris GS115, but the lower secretion level limits its industrial application. This study attempts to increase the secretion level of prochymosin through N-glycosylation, and explore the molecular mechanism of N-glycosylation affecting secretion. Adding an N-glycosylation site at the 34th amino acid of the propeptide of prochymosin significantly increased its secretion in P. pastoris. N-glycosylation improved the thermostability of prochymosin without affecting the enzymatic activity. Immunoprecipitation coupled to mass spectrometry (IP-MS) analysis showed that compared with the wild prochymosin (chy), the number of proteins interacting with N-glycosylated mutant (chy34) decreased, and all differential interacting proteins (DIPs) were down-regulated in chy34-GS115 cell. The DIPs in endoplasmic reticulum were mainly concentrated in the misfolded protein pathway. Among the five DIPs in this pathway, overexpression of BiP significantly increased the secretion of chy. The knockout of the possible misfolded protein recognition elements, UDP-glycose:glycoprotein glucosyltransferase 1 and 2 (UGGT1/2) had no effect on the growth of yeast cells and the secretion of prochymosin. In conclusion, N-glycosylation increased the secretion of prochymosin in P. pastoris trough the adjustment of intracellular interacted proteins. The results of our study may help to elucidate the molecular mechanism of N-glycosylation affecting secretion and provide a new research method to improve the secretion of heterologous glycoprotein in P. pastoris.